INVESTMENT OPPORTUNITY SET, PERSISTENSI LABA DAN FAKTOR LAINNYA TERHADAP KUALITAS LABA - Yustinus Andrey Setiawan; Paulina Sutrisno (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research was conducted with the aim of analyzing the factors that influence earnings quality. The dependent variable used in this research is earnings quality. The independent variables used in this research are leverage, profitability, institutional ownership, managerial ownership, investment opportunity set, earnings persistence, and firm size. The population of this research are all manufacturing companies that are consistently listed on Indonesia Stock Exchange during the period of 2019 – 2021. This research uses a purposive sampling method in sampling. 43 companies met the research criteria, so that is 129 data used as research samples. This research uses a multiple regression analysis model to examine the relationship between the independent variables on the dependent variable. The results of this research indicate that firm size has a positive effect on earnings quality, while 6 other variables such as leverage, profitability, institutional ownership, managerial ownership, investment opportunity set, and earnings persistence have no effect on earnings quality.